ANALISIS FAKTOR PENGARUH KEPUASAN MAHASISWA DAMPAKNYA PADA LOYALITAS MAHASISWAUNIVERSITAS PEMBANGUNAN NASIONAL “VETERAN” JAKARTA - Heni Nastiti; Dahlia Br. Pinem (Ekonomi dan Bisnis, 2014)
The study, entitled Analysis of Student Satisfaction Factors Impact On National Development University Student Loyalty "Veteran" Jakarta. To determine and analyze the influence of perceptual capabilities of employees, faculty performance against its impact on student satisfaction student loyalty either jointly or individually. This study is based on previous research and theories relevant capabilities of employees, faculty performance, student satisfaction and student loyalty by using the research method of descriptive analysis, correlation and path analysis (Path Analysis). Population studies students at the University for National Development "Veteran" Jakarta with sampling proportional stratified random sampling in the Faculty of Economics, Faculty of Law and Faculty of Social and Political Sciences as many as 168 respondents. From the analysis of the validity and reliability of all the questions to the variable capabilities of employees, faculty performance and student satisfaction and student loyalty is valid and reliable. Based on the analysis and hypothesis testing sub-structure have a significant effect on the capability of employees is 50.10%, 38.30% of faculty performance and jointly by 65.40%. While the sub-structure capability -2 influence employees at 13.70%, 30.90% of faculty performance and student satisfaction by 0.219 or 21.90% and jointly by 36.10% means that individually and jointly variable employee capabilities and performance of the faculty must still be improved, thereby increasing the satisfaction and loyalty of students at the University for National Development "Veteran" Jakarta. It is recommended to conduct further research on the influence of student satisfaction and loyalty beyond the capabilities of employees and performance variables lecturer at the University for National Development "Veteran" Jakarta.